The clinical and imaging features of cerebrotendinous xanthomatosis: A case report and review of the literature. Issue 9 (5th March 2021) - Ma, Chi; Ren, Yan-De; Wang, Jia-Chen; Wang, Cheng-Jian; Zhao, Ji-Ping; Zhou, Tong; Su, Hua-Wei
Abstract: Rationale: Cerebrotendinous xanthomatosis (CTX) is a rare autosomal recessive lipid deposition disorder characterized by systemic signs and neurological dysfunction. The radiological features of CTX are infrequently summarized in the literature. Patient concerns: We described a 40-year-old male patient who repeatedly engaged in wrestling matches and presented with progressive difficulty in walking and reduced balance with egg-sized, hard, smooth, and painless masses in both ankles. Diagnosis: Neuroimaging examination showed abnormalities both supra- and infratentorially. Bilateral ankle joint magnetic resonance imaging showed bilateral xanthomata of the Achilles tendon. The diagnosis was confirmed by the detection of a sterol 27-hydroxylase gene mutation. Interventions: The patient was treated with chenodeoxycholic acid (250 mg 3 times per day). Outcomes: To date, the patient's bilateral xanthomas of the Achilles tendon have begun to diminish, and his neurological impairment has not deteriorated further but has not yet improved. Lessons: We report a rare case of CTX and summarize the clinical and imaging features of this disease. Our findings suggest that the abnormal signals in the dentate nucleus or a long spinal cord lesion involving the central and posterior cord, combined with tendon xanthoma, are important clues for the diagnosis of CTX.